Distributive conflict and the end of Brazilian economy's "Brief Golden Age" - Franklin Serrano; Ricardo de Figueiredo Summa (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2022)
The aim of this paper is to discuss the main causes of the interruption of the process of socially inclusive growth that occurred in the Brazilian economy from the mid-2000s, which we will call the Brazilian economy's "Brief Golden Age". Our analysis is based on two central hypotheses. The first is that, for a number of structural reasons, this process generated an "undesired revolution" in the Brazilian labor market, which strengthened workers' bargaining power and generated a tendency of real wages growing more than productivity. The second is that the interruption of this process of socially inclusive growth from 2015 onwards occurred as an effect of this intensification of the distributive conflict, indirectly, by the political pressure exerted by the capitalist class (and its allies) on the government to change the economic policy stance and create conditions for the resolution of the distributive conflict in favor of capital, and not for economic or political effects acting directly on private investment.
Keywords: B51; D30; E11; P16; 330; distributive conflict; induced investment; political economy; Brazilian economy